Chrystyjansʹke svidčennja u sviti, povnomu fašystiv = Christian Witness in a World Full of Fascists - Penner, Majron Bredli (Bogoslovs'ki rozdymi, 2022)
Today I will begin to explore with you the question of what Christian witness looks like today, in the context of violent ideological aggression and war. And I must acknowledge right from the start: I am keenly aware of my location - safe and secure in Canada - and of the location of many of you, who are suffering in the midst of a heinous and brutal war, and in constant and imminent danger of its threats (or at least have loved ones caught in the midst of this horrible aggression). So I am aware, then, that in many respects you are my teachers in regard to my principal question here. All I can hope to do is explore with you what I learn from Holy Scripture and from those who have reflected deeply on it (principally from the study of Kierkegaard and Bonhoeffer). I trust that that these meagre reflections will have meaning for you as you seek to be faithful under these incredibly difficult circumstances.